Expression of structural proteins and angiogenic factors in normal arterial and unruptured and ruptured aneurysm walls - (:unkn) unknown (My University, 2005)
OBJECTIVE: To identify differences in the expression of certain structural proteins and angiogenic growth factors in vessel tissues that represent different phases of the process of intracranial aneurysm formation and rupture: normal vessel wall, intact (unruptured) aneurysm wall, and ruptured vessel wall. METHODS: The novel study design involved 10 pairs of specimens (ruptured and unruptured aneurysm wall) obtained perioperatively during clipping operations in 10 patients with multiple aneurysms. All surgeries were performed within 5 days of subarachnoid hemorrhage. As controls, five circle of Willis specimens were obtained from five cadavers. Sections of each of the 25 specimens were separately immunostained for five structural proteins (collagen Types III and IV, alpha-smooth muscle actin, fibronectin, and laminin) and three angiogenic factors (vascular endothelial growth factor, basic fibroblast growth factor, and transforming growth factor-alpha). Levels of expression for each protein and factor were graded, and the average grades for each tissue group were recorded and compared. RESULTS: Among the structural proteins studied, fibronectin specifically is densely expressed in ruptured aneurysms, which is graded as 2.0. However, its expression is less prominent both in nonaneurysmal vessel wall (Grade 1.0) and unruptured aneurysm vessel wall (Grade 1.1). Contrary to fibronectin, laminin is more intensely and regularly expressed in normal vessel wall (Grade 2.7) than in ruptured (Grade 1.1) and unruptured (Grade 1.0) aneurysmal specimens. Among the angiogenic growth factors studied, transforming growth factor-alpha shows a peculiar grading of staining, different from the other two angiogenic factors examined, so that it is more highly expressed in normal circle of Willis specimens (Grade 2.1) than in unruptured and ruptured aneurysm walls, graded as 0.5 and 0.6, respectively. CONCLUSION: Normal vessel wall, unruptured aneurysm wall, and ruptured aneurysm wall exhibit different levels and patterns of expression for the structural proteins and regulator growth factors investigated. If one accepts the premise that immunohistochemical study has its inherent methodological problems, these results suggest that the biological mediators of aneurysm formation in a vessel wall differ from those of the biological mediators of aneurysm rupture. There was a novel finding related to fibronectin and laminin: the results indicated that a rise in the fibronectin-to-laminin ratio in an unruptured aneurysm wall may contribute to rupture. A drop in transforming growth factor-alpha expression in a vessel wall may also contribute to aneurysm formation.
Keywords: Adult; Female; Humans; Middle Aged; Male; Retrospective Studies; Immunohistochemistry; Case-Control Studies; Endothelium, Vascular; Fibronectins; Intracranial Aneurysm; Aneurysm, Ruptured; Gene Expression; Membrane Proteins; Actins; Collagen Type III; Collagen Type IV; Laminin; Growth Substances; Extracellular Matrix